Hubungan Pengetahuan, Peran Keluarga Dan Kepemilikan Jaminan Kesehatan Dengan Pemilihan Penolong Persalinan Pada Ibu Hamil Di Desa Batuhideung Kecamatan Cimanggu Pandeglang Banten Tahun 2022: Relationship Between Knowledge, Family Role, and Ownership of Health Insurance with the Selection of Birth Assistance for Pregnant Women in Batuhideung Village, Cimanggu Pandeglang District, Banten in 2022 - Julaeha, Euis (Dohara POAJ, 2023)
Introduction: The selection of birth attendants is one of the reproductive rights of individuals in determining where to give birth and who will assist in childbirth. Many factors influence the selection of birth attendants, including maternal knowledge, family roles, and BPJS card ownership. In the Cimanggu Health Center in 2021 48,7% of mothers were assisted by midwives, while 50,3% of mothers who gave birth were assisted by traditional birth attendants. The purpose of the study was to determine the relationship between knowledge, family roles, and health insurance ownership with the selection of birth attendants for pregnant women in Batuhideung Village, Cimanggu District, Pandeglang Banten in 2022. Methods: The research method used was quantitative analysis using a cross-sectional approach using primary data, the number of samples was as much as 52 third-trimester pregnant women, total sampling technique, data analysis using Chi-Square test. Result: The results of the univariate analysis revealed that the selection of birth attendants for pregnant women was mostly by health workers (midwives) 63,5%; with good knowledge of 55,8%; the role of the family supporting 71,2% and the ownership of BPJS Health was 65,4%. Based on the results of the chi-square test, there was a significant relationship between knowledge (p = 0,000); family roles (p = 0,011); and BPJS Health ownership (p = 0,000) with the selection of birth attendants for pregnant women. Discussion: The conclusion of the study there is a significant relationship between knowledge, family roles, and ownership of BPJS Health with the selection of birth attendants for pregnant women. It is hoped that mothers and families can provide mutual support in choosing delivery assistance assisted by health workers, besides having a BPJS card so that mothers and families feel calm during childbirth because they get cost waivers.